Investigating the Role of Physical Education in Chinese Universities to Produce Skillful Athletes - GUI Yulong; An Jing, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2021)
Physical education is a term often used as a connotation for physical fitness. A physical education curriculum is necessary for producing skillful athletes. This study examines the impact of physical education on skillful athletes with respect to factors like Diet, Courses/Practices, Stress Management, Drinking/Smoking, and Physical Activities in Childhood, with Physical Activity in a moderating role of fitness. Respondents of this study were students of physical education in Chinese universities. Data of this quantitative research study was collected through the drop-down survey method by adopting a convenient sampling technique. The data was cross-sectional so Smart PLS software was used for analysis. Results revealed that factors related to physical education like (Diet, Courses/Practices, Stress Management, Drinking/Smoking, Physical Activities in Childhood, Physical Activity) have a positive and significant impact on producing skillful athletes in Chinese universities. It was also found that the fitness of athletes moderates the relationship between these factors and skillful athletes in Chinese universities. This study recommends that for producing skillful athletes, the Chinese universities must also focus on other related factors of physical education like Diet, Courses/Practices, Stress Management, Drinking/Smoking, and Physical Activities in Childhood, Physical Activity along with curriculum and other subjects.